Prices in Great Britain (Quarterly Journal of Economics, 1887)
Journal Article Appendix Get access The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 385–399, https://doi.org/10.2307/1882767 Published: 01 April 1887